Design and Implementation of a Secondary Surveillance Radar/Identification Friend or Foe Transceiver Card - Alsaif, Saleh (Department of Electrical Engineering, 2015)
The performance of SSR/IFF equipment, i.e. the transponder or the interrogator, can be tested by means of an SSR/IFF test set, which is usually extremely expensive, hard to transport and requires end-user certificates. This dissertation thus focuses on the design and implementation of a short-range real- time SSR/IFF Transceiver Card (ITRC), which can be used as an experimental platform for SSR/IFF test applications. User requirements are provided and analysed, resulting in a system breakdown structure, where for each subsystem a summary of related concepts is presented in order to produce the technical requirements for the system. The hardware was designed to be smaller, lighter, less expensive and easy to repair than conventional SSR/IFF test sets. When it has been integrated with an existing SSR/IFF reply emulator, it is capable of generating and analysing RF SSR/IFF signals for modes 1, 2, 3/A, C and secure mode 4 at a frequency of 1030 MHz and 1090 MHz in order to test the functionality of the interrogator and transponder. Verification for the design was accomplished by testing the transceiver hardware and then integrating the system with SSR/IFF transponder and interrogator. The results achieved were found to be compliant with the user requirements.